การสร้างเครื่องวัดสนามแม่เหล็กเชิงอะตอมเพื่อการประยุกต์ ในทางชีวการแพทย์ - กิตติพงศ์ ปันธินวน (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Atomic magnetometer has been developed to have high sensitivity of 12 10 / z T H − or better, which is in the range of the magnetic signals from human organs, such as heart and brain. The ultimate goal of this project is to construct an atomic magnetometer based on rubidium vapour cell with sensitivity of 10 12T / Hz − . For this kind of magnetometer, the optical pumping of rubidium vapour is an important process for measuring magnetic fields. Therefore, we designed and constructed essential parts of the atomic magnetometer, including light source, Helmholtz coils, temperature controller and photodetector for optical pumping experiment. Each part was tested, and the results of its measured characteristics were showed and discussed. From our experiment set up, we attempted to determine the density of rubidium vapour as a function of temperature by measuring the intensity of linearly polarized light via rubidium vapour cell. The results showed the intensities of the transmitted laser decreased abruptly at 318K when the temperature increased by 2 K from room temperature to 323K, and increased at 314K when the temperature decreased from 323K to room temperature during naturally cooling down. We suggested that the suddenly changes of laser intensity strongly correlate with the melting point of rubidium at 312.45K. We believe that the progress achieved here pave the way to the success in the construction of atomic magnetometer.